DESIGN OF PERKUWEN BRIDGE PART WAY LONG IKIS-LAMBAKAN PASER TANA PASER REGENCY PROVINCE EAST KALIMANTAN - Humaira Afrila; Markawie Markawie (CERUCUK, 2018)
Long Kali is a sub-district of Paser Tana Paser Regency Prov. East Kalimantan. In this sub-district have two village separate by a river, that is Perkuwen river, there is bridge has a broke. Whereas the village very needed a bridge because it is used as a transportation infrastructure for peoples and also passed by vehicles transporting oil palm yields . Therefore, the design of composite bridges made with spans 25 m and 7 m wide bridge.In this plan the analysis of Standard methods of loading refers to the bridge imposition For RSNI T-02-2005 about composite bridge structure design method, refers to RSNI T-03-2005 about Steel Structural Design For Bridge, SNI 03-1729-2002 about Steel Structures Planning Procedures and SNI 03-2847-2002 about Concrete Structures Calculation for Building.The result is used the main girder profile SH 950 x 400 x 16 x 32 and diaphragm WF 400 x 200 x 8 x 13. Vehicle floor plate thickness 20 cm using quality concrete  30 MPa and quality reinforcing steel reinforcement  360 MPa with subject dividers reinforcement D22- 100 and D12-100 mm. In using concrete pavement  30 MPa D22-100 mm staple reinforcement and shear reinforcement rebars quality D12-100 mm  360 MPa. Concrete abutment in the form  25 MPa at 2 m height and length of 8,5 m. Steel pipe pile foundations quality  25 MPa are 16 pieces with a length of 10 meters and a diameter of 0.4 m.Keyword: Bridge, composite, steel pipe pile.